2020
DOI: 10.54203/scil.2020.wvj81
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Virulence Genes and Antifungal Resistance in Candida albicans Isolated from Raw Goat Milk

Abstract: The contamination of goat milk with pathogenic fungi can cause health hazards for the consumers either they consume it raw or even in the processed form. Since there are few studies concerning yeasts in raw goat milk, the present study aimed to determine the prevalence of yeasts and isolate Candida albicans from raw goat milk samples. Also, this study determined the distribution of virulence genes and the antifungal susceptibility profile of Candida albicans isolates. A total of 30 goat milk samples (collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(34 reference statements)
0
1
1
Order By: Relevance
“…The present result contrasted with the result of Shrief et al (2019) who examined the virulence genes of C. albicans and found that HWP1 gene represented (77%), SAP1 (65%), and PLB1 (52%). Also, these results are contrasted with Soliman et al (2020) who discovered that 50% of C. albicans isolates had HWP1 and SAP4, while PLB1 was not detected in tested isolates (0%).…”
Section: Molecular Identification Of C Albicanscontrasting
confidence: 85%
“…The present result contrasted with the result of Shrief et al (2019) who examined the virulence genes of C. albicans and found that HWP1 gene represented (77%), SAP1 (65%), and PLB1 (52%). Also, these results are contrasted with Soliman et al (2020) who discovered that 50% of C. albicans isolates had HWP1 and SAP4, while PLB1 was not detected in tested isolates (0%).…”
Section: Molecular Identification Of C Albicanscontrasting
confidence: 85%
“…Previous studies in Egypt have reported a higher prevalence of HWP1 and ALS1 genes in C. albicans isolates from patients ( Shrief et al., 2019 ; Hamady and Marei, 2021 ). Additionally, another study revealed that RAS1 and ALS1 were present in all Candida isolates, while HWP1 and SAP4 were found in half of the isolates ( Soliman et al., 2020 ). In addition, Inci et al.…”
Section: Discussionmentioning
confidence: 99%